Практики, традиции и границы европейской интеграции - Волков, В. (Социология: теория, методы, маркетинг, 1999)
The major assertion of the paper is that social integration rests on shared practices, habits, and traditions. The concepts of practical knowledge and style within the context of pragmatic approach to norms and rules enabled social theorists to reconsider the idea of tradition. So one of the main tasks of sociology in the face of European integration is to takeinto account a variety of local traditions and their long lasting impact in historical development of particular societies.